Applied behavioral analysis for the skill performance of children with autism spectrum disorder - Silva, Alan Patricio da; Bezerra, Italla Maria Pinheiro; Antunes, Thaiany Pedrozo Campos; Cavalcanti, Matheus Paiva Emidio; Abreu, Luiz Carlos de (Frontiers in Psychiatry, 2023)
INTRODUCTION: Autism Spectrum Disorder has characteristics observed over time the difficulty of affective, sensory, and emotional processing, which triggers a series of difficulties in the individual, and limits him in many aspects of his development, a neurological disorder that is characterized by deficits in communication, social interaction, with specific patterns concerning restricted and repetitive interests. OBJECTIVE: to evaluate the therapeutic strategy applied for the treatment of patients diagnosed with autism. METHOD: this is a retrospective descriptive study with individuals diagnosed with autism undergoing treatment at a therapeutic clinic in the metropolitan region of São Paulo, called Grande ABC. With a database of 16 patients with regular treatment between 6 months and 12 months of treatment, the performance of patients in 3 periods over the treatment time was compared based on the domains of skills registered in the ABA+ affective intelligence software. Seventeen participants in the convenience sample were included in the study, distributed and analyzed according to individual performance throughout the therapy period, as well as the variables observed in the skill groups Activity of daily living, attention skills, pre-academic skills, and skills. social. RESULTS: the age range of study participants ranged from 3.8 years to 10.8 years, 70% of participants are male (10) and female (6), both with a treatment period of more than 6 months of intervention. The evolution of skills can be observed between the T0 and T1 intervals, with an improvement in the skill gain over the observed period. CONCLUSION: the strategy applied based on the ABA methodology improved the performance of patients over the period observed.